2021
DOI: 10.1002/acm2.13370
|View full text |Cite
|
Sign up to set email alerts
|

Surface guided frameless positioning for lung stereotactic body radiation therapy

Abstract: Background and purpose When treating lung tumors with stereotactic body radiation therapy (SBRT), patient immobilization is of outmost importance. In this study, the intra‐fractional shifts of the patient (based on bony anatomy) and the tumor (based on the visible target volume) are quantified, and the associated impact on the delivered dose is estimated for a frameless immobilization approach in combination with surface guided radiation therapy (SGRT) monitoring. Methods Cone beam computed tomographies (CBCT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The shift of the patient (bony anatomy) in the CBCTs intra-fractionally was ≤2 mm for 132/137 fractions in the vertical (vrt) and lateral (lat) directions, and 134/137 fractions in the longitudinal (lng) direction and ≤4 mm in 134/137 (vrt) and 137/137 (lat, lng) of the fractions. The shift of the tumour was ≤2 mm in 116/137 (vrt), 123/137 (lat) and 115/137 (lng) fractions and ≤4 mm in 136/137 (vrt), 137/137 (lat), and 135/137 (lng) fractions [7] .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The shift of the patient (bony anatomy) in the CBCTs intra-fractionally was ≤2 mm for 132/137 fractions in the vertical (vrt) and lateral (lat) directions, and 134/137 fractions in the longitudinal (lng) direction and ≤4 mm in 134/137 (vrt) and 137/137 (lat, lng) of the fractions. The shift of the tumour was ≤2 mm in 116/137 (vrt), 123/137 (lat) and 115/137 (lng) fractions and ≤4 mm in 136/137 (vrt), 137/137 (lat), and 135/137 (lng) fractions [7] .…”
Section: Resultsmentioning
confidence: 89%
“…Saduris et al reviewed 137 fractions delivered to 25 lung cancer patients treated free breathing [7] . Patients were set-up using SG, then the bony anatomy checked using orthogonal kV imaging and any additional shifts made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review only found 4 publications with clinical data in relation for patient set up and intra-fraction motion monitoring [17] .  Sarudis et al [18] examined 137 fractions delivered to 25 patients using surface guidance. The intrafractional motion using CBCT was ≤2 mm for 132/137 fractions in the vertical and lateral directions, and 134/137 fractions in the longitudinal direction.…”
Section: Discussionmentioning
confidence: 99%
“…It enabled us to visualize important anatomical details in the patient's body. Additionally, many recent studies have shown that optical body surface monitoring can also assess the patient's setup error, especially in breast cancer patients (28,29). Theoretically, the target volume is closer to the chest wall for PMRT patients than the patients undergoing breast-conserving therapy, which makes the effect of SGRT more robust and accurate.…”
Section: Discussionmentioning
confidence: 99%